Associations of neutrophil-to-lymphocyte ratio with intracranial and extracranial atherosclerotic stenosis - Xie, Yu; Liu, Zhenxing; Dan, Bitang; Zou, Li; Zhang, Lei; Zhang, Renwei; Li, Huagang; Cai, Qi; Aiziretiaili, Nadire; Ren, Shanling; Liu, Yumin (Frontiers in Neurology, 2022)
Background: Neutrophil-to-lymphocyte ratio (NLR) has been shown to be an important inflammatory maker. This study aims to investigate the association of NLR with intracranial and extracranial atherosclerotic stenosis. Methods: We retrospectively recruited patients who underwent digital subtraction angiography (DSA) for evaluating intracranial/extracranial stenosis in Zhongnan Hospital of Wuhan University from January 2017 to October 2021. Clinical characteristics, DSA data, blood routine and lipid profile were recorded. Logistic regression was used to evaluate the association of NLR and intercranial/extracranial atherosclerotic stenosis in three aspects: distribution of stenosis, whether stenosis is symptomatic and degree of stenosis. Results: A total of 1129 patients were included in our analysis, with median age of 62 years (interquartile range 55-68), and median admission NLR 2.39 (interquartile range 1.84-3.42). 986 patients presented intracranial and/or extracranial atherosclerotic stenosis. Increased NLR were associated with intracranial stenosis [odds ratio (OR), 1.54; 95% confidence interval (CI), 1.27-1.85; p<0.001], extracranial stenosis (OR, 1.56; 95%CI, 1.25-1.96; p<0.001), and combined intracranial/extracranial stenosis (OR, 1.61; 95%CI, 1.28-2.03; p<0.001). After adjustment of potential factors, higher NLR were independently associated with symptomatic stenosis (OR, 1.16; 95%CI, 1.05-1.27; p=0.003) and degree of stenosis (OR, 1.32; 95%CI, 1.17-1.49; p<0.001). Compared with the first quartile NLR, the second, third and fourth quartiles NLR were independent risk factors for symptomatic stenosis and stenosis degree (both p for trend <0.001). Conclusion: Increased NLR is an important factor associated with both intracranial and extracranial atherosclerotic stenosis. Patients with symptomatic intracranial/extracranial atherosclerotic stenosis or more severe degree of stenosis presented elevated NLR level.